2013
DOI: 10.2478/mms-2013-0007
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Coordinate Measuring Machine Built Using Lasertracer System and Spherical Standard

Abstract: Improvements of modern manufacturing techniques implies more efficient production but also new challenges for coordinate metrologists. The crucial task here is a coordinate measurement accuracy assessment. It is important because according to technological requirements, measurements are useful only when they are stated with their accuracy. Currently used methods for the measurements accuracy estimation are difficult to implement and time consuming. It is therefore important to implement correct and validated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Alternatively, laser tracer systems can be used, which are well known for the calibration of coordinate measuring machines. 20 These coordinate measurement calibration procedures are not yet considered in the present simulations since the intention was to investigate the basic effects and show the demands on the positioning. To achieve an uncertainty of 0.01 MTF units, simulations have shown that an accuracy of the axial detector position in the range of the step size of the through-focus curve (250 nm) seems to be sufficient for sample lens 2.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, laser tracer systems can be used, which are well known for the calibration of coordinate measuring machines. 20 These coordinate measurement calibration procedures are not yet considered in the present simulations since the intention was to investigate the basic effects and show the demands on the positioning. To achieve an uncertainty of 0.01 MTF units, simulations have shown that an accuracy of the axial detector position in the range of the step size of the through-focus curve (250 nm) seems to be sufficient for sample lens 2.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is certainly possible to create an application which would automatically detect the optimal placement of a measured workpiece using the discussed model and additional data concerning the shape of the object. It could also be possible to combine this application with the module responsible for the simulation of probe head errors (like the one presented in [36]), which would allow to limit All values are given in mm measurement uncertainty even further by suggesting the optimal number of probing points and their distribution. In this way, it should be possible to definitely design the most optimal measurement strategy.…”
Section: Resultsmentioning
confidence: 99%
“…Further examples proving its possible application for this task can be found in [34,36]. The model could also be of use for determining the optimal position of a measured workpiece in the measuring volume of the machine.…”
Section: Modeling Of Kinematic System Residual Errorsmentioning
confidence: 99%
“…Usually, to verify vision-based system accuracy, measurements are also performed on more precise metrological devices, such as coordinate measuring machines [21,22] or Laser Tracker systems and then compared. The CMMs are widely used for industrial dimensional validation, but their measurement speed is too slow for 100% in-line inspection.…”
Section: Introductionmentioning
confidence: 99%